Cover Picture: Prussian Blue Modified Submicron Structured Gold Electrodes for Amperometric Hydrogen Peroxide Sensing (Electroanalysis 3/2018). Issue 3 (13th March 2018) - Lu, Si‐Yuan; Chen, Yihao; Fang, Xufei; Feng, Xue
Abstract : The cover picture shows the fabricating structure, working principle and performance of the sub‐micron porous gold/PB sensor for detecting the H2 O2 concentration, which gains much higher sensitivity, lower LOD and better long‐time stability than that of flat Au/PB. More details are discussed in the article by Siyuan Lu, Yihao Chen, Xufei Fang and Xue Feng. DOI:10.1002/elan.201700754.